Perceptions on radioprotective garment usage and underlying reasons for non-adherence among medical radiation workers from public hospitals in a middle-income Asian setting: A qualitative exploration - Mohd Ridzwan, Siti Farizwana; Bhoo-Pathy, Nirmala; Isahak, Marzuki; Wee, Lei Hum (Elsevier, 2019)
Background: Radioprotective garments protect medical radiation workers from exposure to radiation at workplace. However, previous studies have found poor adherence to the use of radioprotective garments. Objectives: We explored the perceptions and practices related to the use of radioprotective garments among medical radiation workers in public hospitals, and sought to understand the reasons for non-adherence. Design and setting: A qualitative approach was applied by conducting face-to-face in-depth interviews with 18 medical radiation workers from three university hospitals using a semi-structured interview guide. Results: Five themes emerged with respect to perceptions on the use of radioprotective garments: (i) the dilemmas in practising radiation protection, (ii) indication of workers' credibility, (iii) physical appearance of radioprotective garments, (iv) practicality of radioprotective garment use, and (v) impact on workflow. Actual lack of radioprotective garment use was attributed to inadequate number of thyroid shield and other garments, radioprotective garments' unsightly appearance including being dirty and defective, impracticality of using radioprotective garments for some nuclear medicine procedures, disruption of workflow because of workers’ limited movements, attitudes of workers, and organisational influences. Conclusion: Medical radiation workers demonstrated a definitive practice of using radioprotective aprons, but often neglected to use thyroid shields and other garments. Availability and hygiene are reported as the core issues, while unclear guidelines on practical use of radioprotective garments appear to lead to confusion among medical radiation workers. To the best of our knowledge, this is the first qualitative study of its kind from a middle-income Asian setting. © 2019